Impact of Earnings Smoothness on Stock Prices, Stock Returns and Future Earnings Changes – the Polish Experience - Jacek Welc (European Financial and Accounting Journal, 2014)
Capital markets appreciate stability. It means that companies reporting smooth earnings patterns tend to be priced relatively high. However, the empirical issue is whether such valuation premiums for earnings smoothness are justified. We examine the relationships between past five-year earnings smoothness and relative stock prices of companies listed on the Warsaw Stock Exchange. The empirical investigation confirmed that on the Polish market the smooth historical earnings are rewarded with valuation premiums and the erratic earnings are penalized with valuation discounts. However, stocks with smooth past earnings tend to bring sub-par future stock returns while stocks with relatively erratic earnings seem to generate above-average returns. Furthermore, the scope of past earnings smoothness does not show any discernible relationships to realized investment risk measures. Finally, companies with smooth earnings tend to report “negative earnings surprises” and relatively slow earnings growth rates in the following year. All in all, our research suggests that there is not any empirically observable justification for the valuation premiums observed in the case of stocks with smooth past earnings because such smoothness translate neither into relatively low future investment risks nor relatively fast future earnings growth.
Keywords: C21; G11; 650; Stock valuation; Stock returns; Earnings smoothness; Valuation multiples